Activation of TRPV1 by Capsaicin or Heat Drives Changes in 2-Acyl Glycerols and N-Acyl Ethanolamines in a Time, Dose, and Temperature Dependent Manner - Manchanda, Meera; Leishman, Emma; Sangani, Kishan; Alamri, Ali; Bradshaw, Heather B. (Frontiers in Cell and Developmental Biology, 2021)
Endocannabinoids (eCBs) and transient receptor potential (TRP) channels are associated with thermoregulation; however, there are many gaps in the understanding of how these signaling systems work together in responding to changes in temperature. TRPV1, a calcium-permeable ion channel, is activated by capsaicin, elevated temperature, the eCB Anandamide, and over 15 additional endogenous lipids. There is also evidence for signaling crosstalk between TRPV1 and the eCB receptor, CB1. We recently found that activation of TRPV1-HEK cells by capsaicin increases the production of the eCB, 2-arachidonoyl glycerol (2-AG), suggesting a molecular link between these receptors. Here, we tested the hypothesis that TRPV1 activation by capsaicin drives regulation of a wider-range of lipid signaling molecules and is time and dose-dependent. We also tested the hypothesis that changes in temperature that drive changes in calcium mobilization in TRPV1-HEK will likewise drive similar changes in lipid signaling molecule regulation. Lipid analysis was conducted by partial purification of methanolic extracts on C18 solid phase extraction columns followed by HPLC/MS/MS. Capsaicin increased the release of 2-acyl glycerols (2-AG, 2-linoleoyl glycerol, 2-oleoyl glycerol), in a concentration- and time-dependent manner, whereas levels of N-acyl ethanolamines (NAEs), including Anandamide, were significantly decreased. Analogous changes in 2-acyl glycerols and NAEs were measured upon ramping the temperature from 37-45°C. In contrast, opposite effects were measured when analyzing lipids after they were maintained at 27°C and then quickly ramped to 37°C, wherein 2-acyl glycerol levels decreased and NAEs increased. These results provide further evidence that the eCB system and TRPV1 have integrated signaling functions that are associated with the molecular response to temperature variation.